Ageless vegan : the secret to living a long and healthy plant-based life - McQuirter, Tracye Lynn; McQuirter, Mary (Da Capo Press/Hachette Book Group, 2018)
"Longtime vegan and author of By Any Greens Necessary offers a plan and recipes to harness the power of a vegan diet for longevity, health, and beauty. Plant-based diets as a means to greater health are on the rise; from Michael Greger, MD, to T. Colin Campbell, PhD, and Neal Barnard, MD, and others, health professionals are embracing a veg-powered way to combat disease. A diet full of plant-based foods can also help you look and feel younger. Food activist, public health nutritionist, and longtime vegan Tracye McQuirter (50-years-old-going-on-30) teams up with her mother Mary (80-years-old-going-on-50) to share their secrets for staying young, vibrant, and healthy (hint: it's all in the greens), along with 100 delicious plant-based recipes. The McQuirters break down the basics of nutrition, how to build a vegan pantry, and how to make sure you're getting the best nutrients to promote longevity and prevent chronic disease, along with 100 recipes that are perfectly seasoned and full of flavor. Based on fresh, easy-to-find ingredients, including 100% whole grains and natural sweeteners, the recipes combine spices and herbs to create rich flavor combinations, like Cajun and BBQ, so you can easily add variety to your everyday meals. With a 14-day plan to jumpstart healthy eating habits, practical advice about transitioning to a vegan diet, getting essential nutrients, socializing with friends, eating healthy on a budget, and more, Ageless Vegan provides the tools for you to dine your way to a long, healthy, and delicious life."--Provided by publisher.